Molecular Detection And Evaluation Of Resistance Of Abaca Hybrid (Bc2) To Bunchy Top Viruses In Eastern Visayas Region Of Philippines (Journal of Plant Disease Sciences, 2020)
Abaca (Musa textilis Nee.), known internationally in commerce as Manila hemp for its world class fiber, is indigenous to the Philippine Islands and one of the most important materials for export in the Philippines (Ocfemia, 1930). One of the major challenges faced by the abaca industry in the Philippines is the infection of abaca bunchy top caused by ABTV, an ssDNA virus transmitted by the aphids (Pentalonia nigronervosa Coq.) which causes major losses on the abaca plantations in the Philippines (Furuya et al., 2006). Bicol and Eastern Visayas were reported to be hot spots for the disease (Raymundo et al., 2001). In Eastern Visayas, the estimated fiber loss was 312,076 kg with a value of Php8,440,350. Northern Samar and Northern Leyte sustain the highest losses, with estimated fiber losses of 153,186 and 116,280 kg valued at Php3,829,650 and Php3,488,400, respectively. Southern Leyte has the
Keywords: Musa textilis; Bunchy Top Virus; Transmission; PCR; Detection; Resistance